PENERAPAN TEKNIK TAILORING PADA BOLA DUNIA TAILOR DI PONDOK KOTA PADANG - Fitri, Corry Paratami; Zahri, Wildati; Yasnidawati, Yasnidawati (Journal of Home Economics and Tourism, 2014)
This research was motivated by the good tailoring techniques are applied to the Bola Dunia Tailor in Pondok City Padang which includes models , materials , patterns and sewing techniques , resulting in a very good quality clothing . This study aims to determine the application of tailoring techniques to Bola Dunia tailor  in  Pondok  CityPadang which includes the application of models , materials , patterns and sewing techniques . The method used is a qualitative case study method . This research was conducted in the  city of Padang , data collection by observation , interviews , and documentation . Data analysis techniques are used , namely data reduction , data presentation and making conclusions . To obtain valid data in a way an extension of the observations , increase persistence , triangulation and auditing . The results of this study revealed that : 1 ) Model fashion tailoring techniques that made ​​Suit ( Suits ), which is also called the Jas . 2 ) The main material used is woll fibrous materials and semi- woll , auxiliary materials ( coatings ) coatings are used first ( Underlining ) consisting of cufner thick and thin , reinforcement material ( Interfacing ) consisting of Vukuda , cufner suits and velvet collar , and the last furing ( Lining ) sateen , complementary materials used are shoulder cushion ( padding ) , and the buttons are large and small . 3 ) The pattern used is a pattern that is constructed directly above the material . 4 ) sewing techniques sewing techniques used are in accordance with the sequence of work steps , such as installing a coating material ( fusing ) , bringing together the parts of suits , and the final settlement is done by using machine tools and manuals .   Kata Kunci: Penerapan, Teknik, Tailoring